Stereoretentive Reactions at the Anomeric Position: Synthesis of Selenoglycosides. Issue 24 (14th May 2018) - Zhu, Feng; O'Neill, Sloane; Rodriguez, Jacob; Walczak, Maciej A.
Abstract: Reported is the stereospecific cross‐coupling of anomeric stannanes with symmetrical diselenides, resulting in the synthesis of selenoglycosides with exclusive anomeric control. The reaction proceeds without the need for directing groups and is compatible with free hydroxy groups as demonstrated in the preparation of glycoconjugates derived from mono‐, di‐, and trisaccharides and peptides (35 examples). Given its generality and broad substrate scope, the glycosyl cross‐coupling method presented herein can find use in the synthesis of selenium‐containing glycomimetics and glycoconjugates. Abstract : Makes Se nse : The stereospecific cross‐coupling of anomeric stannanes with symmetrical diselenides delivers selenoglycosides with exclusive anomeric control. The reaction proceeds without the need for directing groups and is compatible with free hydroxy groups as demonstrated in the preparation of glycoconjugates, saccharides, and peptides. Given its generality and broad substrate scope, the presented method can find use in the synthesis of selenium‐containing glycomimetics and glycoconjugates.